Domestic Organic Waste Composting in Madhyapur Thimi, Bhaktapur - Aryal, Jagannath; Tamrakar, Anand Shova (Nepal Journal of Science and Technology, 2013)
Organic waste composting is an important waste management practice that can reduce the volume of municipal solid waste and increase crop productivity. A study was carried out in Madhyapur Thimi, Bhaktapur in order to develop understanding of different methods of composting for sustainable solid waste management practices. Solid waste was collected randomly from 50 households in the area and segregated manually. The biodegradable waste was composted through pile (aerobic), aerobic bin, anaerobic (pit) and vermicomposting process. The physico-chemical and microbial analysis of composts were carried out in laboratory whereas significance of composts on crop productivity was tested in the study area. The study showed that 81.4% of the waste generated was biodegradable. The physico-chemical and microbial analyses of the compost samples showed pH range of 7.6 to 8.2 and moisture content of 54.5% to 69.5% for different composts. The maximum temperature (62°C) was observed in aerobic (pile) composting. The nutrient analysis (oganic matter, nitrogen, phosphorus, potassium and C: N ratio) of different composts showed that vermicompost was the most among all the composts. The total bacterial and fungal count varied from 3.91 x 104 to 8.05 x 106 cfu/g and 1.30 x 103 to 3.25 x 104 cfu/g respectively. The vermicompost was found rich in microbial population too. The application of vermicompost at 6.25 mt/ha in the study area resulted in increasing in height, diameter and yield of cauliflower by 15.62%, 37.58% and 38.95% respectively over farm yard manure. The height, diameter and yield of cauliflower grown in different composts was found to be significantly different (P<0.05). Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 129-136 DOI: http://dx.doi.org/10.3126/njst.v14i1.8933